2017
DOI: 10.1158/1535-7163.mct-16-0721
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Patient-Derived Xenografts in Colorectal Cancer

Abstract: Developing realistic preclinical models using clinical samples that mirror complex tumor biology and behavior are vital to advancing cancer research. While cell-line cultures have been helpful in generating preclinical data, the genetic divergence between these and corresponding primary tumors has limited clinical translation. Conversely, patient derived xenografts (PDXs) in colorectal cancer (CRC) are highly representative of the genetic and phenotypic heterogeneity in the original tumor. Coupled with high-th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 54 publications
4
54
0
Order By: Relevance
“…Similarly, caution is warranted in highly selected datasets where molecular distributions are expected, or known, to severely deviate from pCRC cohorts, including metastatic samples 42 . Importantly, for both organoids and PDXs, it has been shown that the models recapitulate the heterogeneity of their original tumors 14 , 15 , 25 . However, to assess potential bias, we recommend analyzing CMS-associations of additional molecular markers, for instance MSI-status and BRAF mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, caution is warranted in highly selected datasets where molecular distributions are expected, or known, to severely deviate from pCRC cohorts, including metastatic samples 42 . Importantly, for both organoids and PDXs, it has been shown that the models recapitulate the heterogeneity of their original tumors 14 , 15 , 25 . However, to assess potential bias, we recommend analyzing CMS-associations of additional molecular markers, for instance MSI-status and BRAF mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The original classifier was developed specifically for primary CRCs (pCRC), and it was recently shown that it fails to identify the CM S1 -immune and CM S4 -mesenchymal groups in cell lines, patient-derived organoids and xenografts (PDX) 15 , 18 20 , due to the absence of human immune-related signatures, stromal components and extra-cellular matrix in cell cultures and animal models 7 , 10 , 18 22 . However, at least some CRC cell lines are mesenchymal-like 5 , 16 , 23 , 24 and both organoids and PDXs can be established with minimal bias in terms of clinical and molecular covariates of the originating tumors 14 , 15 , 25 . This indicates that the apparent lack of CM S4 -like models is not a result of biological adaptation to or selection for culturing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These results revealed that the engraftment rate of PDXs was different according to implanted tumor types. PDX models are currently established in variety of cancers, including colorectal 23 , pancreatic 24 , breast 25 , lung 26 , prostate 27 and ovarian cancer 28 . However, reports about PDX models of HCC were rare.…”
Section: Discussionmentioning
confidence: 99%
“…These samples are obtained fresh from tumor and should be implanted as soon as possible within the first 24 h (Rashidi et al, 2000;Fu et al, 1991). PDX has the advantage Full-size  DOI: 10.7717/peerj.9045/ fig-4 that the animal receives the full tumor repertoire from the patient: tumor and the peritumoral inflammatory reaction (Katsiampoura et al, 2017). Additionally, these would be appropriate to trial personalized treatments: the patient's tumor is transplanted in a series of animals that are treated with diverse drugs, and the one which best controls the tumor would be used in the patient (Okada, Vaeteewoottacharn & Kariya, 2018;Williams, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these would be appropriate to trial personalized treatments: the patient's tumor is transplanted in a series of animals that are treated with diverse drugs, and the one which best controls the tumor would be used in the patient (Okada, Vaeteewoottacharn & Kariya, 2018;Williams, 2018). Nevertheless, this method has its limitations as well: it requires the use of animals that lack an immune system, the stroma that forms is murine and not human, and sometimes does not develop metastases (Katsiampoura et al, 2017). In addition, its clinical use is not without difficulties: with slow tumor growth, it has to be transferred to other animals to have a sufficient number for treatments, need for controls and costs involved.…”
Section: Discussionmentioning
confidence: 99%